Enhancement of Blood Cholesterol Level Relating to Edible Reused Cooking Oil Uptake in White Experimental Albino Rats (Global Journal of Science Frontier Research, 2020)
Reusing cooking oil in food preparation, especially during deep-frying is a common practice to save costs. Repeated heating of the oil accelerates oxidative degradation of lipids leading to severe changes in lipid profile of the blood and forming hazardous reactive oxygen species which depletes the natural antioxidant contents of the cooking oil leading to pathologies such as hypertension, diabetes and vascular inflammation. The main objective of this work is to investigate the effect of the reused edible cooking oil uptake with the plasma cholesterol level in some experimental animals. Twenty adult male swiss albino (SWR)rats, weighing 120-200g body weight were housed within the premises of the medicinal and aromatic plant research institutes, national center for research Khartoum. They were randomized to one of the following experimental groups, with five animals per group: Group 1 the Normal group were administered normal diet (control group), Group 2 the experimental group were administered high-fat diet with low dose reused oil injection, Group3 the experimental group were administered high-fat diet with high dose reused oil injection , Group4 the experimental group were administered high -fat diet (disease group).
Keywords: cholesterol level; reused oil; albino rats; normal group and disease group